Output voltage and level control algorithm during submodule fault of modular multilevel converter for HVDC transmission system - Alim, M. A.; Khan, M. A. G.; Munjer, M. A.; Kabir, Sumaiya (2016 IEEE International WIE Conference on Electrical and Computer Engineering (WIECON-ECE), 2016)
This paper presents a new algorithm which automatically tracks submodule fault and on the basis of submodule fault reduces the number of level and output voltage of modular multilevel converter (MMC) in high-voltage DC transmission system. Carrier and Signal (reference) Magnitude Control Sinusoidal Pulse Width Modulation (CSMC-SPWM) technique is used to generate gate pulses of the MMC converter. This CSMC-SPWM technique is used for running the converter under normal condition and also generates pulses for the faulty Sub-Modules (SM) to bypass the supply voltage to un-faulty SMs and decrease the level of operation as well as converter output voltage so the converter remains in operating conditions during the large number of submodule fault. The simulation results show that MMC operates well to any level of operation and faulty SMs are completely removed from any phase of the inverter with lower output voltage.